Menopausal hormone therapy and risk of dementia: health insurance database in South Korea-based retrospective cohort study - Yuk, Jin-Sung; Lee, Jin San; Park, Joong Hyun (Frontiers in Aging Neuroscience, 2023)
Introduction Menopausal hormone therapy (MHT) is used to alleviate the symptoms associated with menopause, despite the lack of recommendations for MHT in preventing dementia. Recent nationwide studies have explored the association between MHT and dementia risk, but the findings remain limited. This study aims to investigate the association between MHT and the incidence of Alzheimer’s disease (AD) and non-AD dementia using national population data from Korea. Methods We conducted a retrospective study using data from the National Health Insurance Service in Korea between January 1, 2002, and December 31, 2019. Women over 40 years were eligible for this study and classified into the MHT or non-MHT groups. The MHT group consisted of women who used Tibolone (TIB), combined estrogen plus progestin by the manufacturer (CEPM), estrogen, combined estrogen plus progestin by a physician (CEPP), and transdermal estrogen during menopause. We compared the risk of dementia between the MHT and non-MHT groups. Results The study included 1,399,256 patients, of whom 387,477 were in the MHT group, and 1,011,779 were in the non-MHT group. The median duration of MHT was 23 months (range: 10–55 months). After adjusting for available confounders, we found that different types of MHT had varying effects on the occurrence of dementia. TIB (HR 1.041, 95% confidence interval (CI) 1.01–1.072) and oral estrogen alone (HR 1.081, 95% CI 1.03–1.134) were associated with a higher risk of AD dementia. In contrast, there was no difference in the risk of AD dementia by CEPM (HR 0.975, 95% CI 0.93–1.019), CEPP (HR 1.131, 95% CI 0.997–1.283), and transdermal estrogen (HR 0.989, 95% CI 0.757–1.292) use. The use of TIB, CEPM, and oral estrogen alone increased the risk of non-AD dementia (HR 1.335, 95% CI 1.303–1.368; HR 1.25, 95% CI 1.21–1.292; and HR 1.128, 95% CI 1.079–1.179; respectively), but there was no risk of non-AD dementia in the other MHT groups (CEPP and topical estrogen). Conclusion Our findings indicate that MHT has varying effects on the incidence of AD and non-AD dementia. Specifically, TIB, CEPM, and oral estrogen alone increase the risk of non-AD dementia, while transdermal estrogen is not associated with dementia risk. It is essential to consider the type of MHT used when assessing the risk of dementia in women.